2012
DOI: 10.1089/lrb.2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Lymphangiogenesis and Angiogenesis During Inflammation in Rat Mesentery Microvascular Networks

Abstract: Background: Lymphatic and blood microvascular systems play a coordinated role in the regulation of interstitial fluid balance and immune cell trafficking during inflammation. The objective of this study was to characterize the temporal and spatial relationships between lymphatic and blood vessel growth in the adult rat mesentery following an inflammatory stimulus. Methods and Results: Mesenteric tissues were harvested from unstimulated adult male Wistar rats and at 3, 10, and 30 days post compound 48/80 stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 25 publications
15
52
0
Order By: Relevance
“…10ā€“12 Lymphatic identity based on these features is supported by our previous co-labeling of lymphatic vessels with lectin or PECAM and typical lymphatic markers: LYVE-1, 8,10ā€“12 Prox1, 10ā€“12 and podoplanin. 10ā€“12 Arterioles, venules, and capillaries were identified by position in the network, vessel morphology, and labeling intensity as previously described. 8 Following printing, MDA-MB-231 cells attached to the tissue substrate and maintained their initially deposited positions.…”
Section: Resultssupporting
confidence: 55%
“…10ā€“12 Lymphatic identity based on these features is supported by our previous co-labeling of lymphatic vessels with lectin or PECAM and typical lymphatic markers: LYVE-1, 8,10ā€“12 Prox1, 10ā€“12 and podoplanin. 10ā€“12 Arterioles, venules, and capillaries were identified by position in the network, vessel morphology, and labeling intensity as previously described. 8 Following printing, MDA-MB-231 cells attached to the tissue substrate and maintained their initially deposited positions.…”
Section: Resultssupporting
confidence: 55%
“…Our results demonstrate an increase in bronchial blood vessels at the time when we observed an increase in lymphatic vessel numbers. Perhaps relevant to this observation are results of Sweat and colleagues who showed that in the mesentery, angiogenesis always preceded lymphangiogenesis (28, 48). Treatment with VEGF-C, the most prominent lymphangiogenic factor, led first to angiogenesis followed by subsequent lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 79%
“…The six lymphatic networks ranged in network area (12-129 mm 2 ), maximum branch order (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and total number of segments (31-219) (Figs. 2; 3A-C).…”
Section: Initial Lymphatic Network Geometriesmentioning
confidence: 99%